2015
DOI: 10.1016/j.nicl.2014.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Cortical thickness abnormalities associated with dyslexia, independent of remediation status

Abstract: Abnormalities in cortical structure are commonly observed in children with dyslexia in key regions of the “reading network.” Whether alteration in cortical features reflects pathology inherent to dyslexia or environmental influence (e.g., impoverished reading experience) remains unclear. To address this question, we compared MRI-derived metrics of cortical thickness (CT), surface area (SA), gray matter volume (GMV), and their lateralization across three different groups of children with a historical diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 90 publications
(135 reference statements)
3
28
0
Order By: Relevance
“…as these studies will impact future policies that promote the health and well--being of children. Finally, our data have important ramifications for understanding typical 60 and atypical brain development as well as for clinical conditions implicating myelin and morphology including autism 61 , dyslexia 62 , and multiple sclerosis 63 .…”
Section: Discussionmentioning
confidence: 87%
“…as these studies will impact future policies that promote the health and well--being of children. Finally, our data have important ramifications for understanding typical 60 and atypical brain development as well as for clinical conditions implicating myelin and morphology including autism 61 , dyslexia 62 , and multiple sclerosis 63 .…”
Section: Discussionmentioning
confidence: 87%
“…Alternative measurements of cortical grey matter anatomical integrity, such as cortical thickness (CT) and surface area (SA) have been used less often for investigating dyslexia [Altarelli et al, 2013;Clark et al, 2014;Frye et al, 2010;Ma et al, 2014]. Here again, the pattern of results is inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Reports vary between lesser [Altarelli et al, 2013;Clark et al, 2014] and greater CT [Ma et al, 2014] in the left fusiform gyrus in dyslexic children, and no CT differences but lower SA in dyslexic adults [Frye et al, 2010]. Other findings include greater CT in the right superior temporal gyrus, planum temporale, middle temporal gyrus, Heschl's gyrus and supramarginal gyrus [Ma et al, 2014]; lesser CT in the left orbitofrontal cortex and in the anterior segment of the superior temporal cortex [Clark et al, 2014], as well as decreased SA in inferior frontal gyrus [Frye et al, 2010]. A recent study [Im et al, 2016] using yet another univariate technique, a graph-based sulcal pattern comparison method, found that the pattern of the sulcal basin area in the left temporo-parietal cortex was atypical in dyslexia.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, training-driven normalization in the left OTC has been found at the functional level, including activation during overt single word reading (Heim et al, 2015) and intrinsic functional connectivity at rest (Koyama et al, 2013). This is in contrast to cortical thickness abnormalities in the same region that persist even after intervention (Ma et al, 2015), which suggest a possible causal impairment in the ventral pathway, at the neuroanatomical rather than neurofunctional level.…”
Section: Behavioral Interventionmentioning
confidence: 93%